Chemical composition of Kelempayan (Neomalarckia cadamba), Sentang (Azadirachta exscelsa) and Acacia (Acacia mangium) / Mohd Sayuti Mohd Ghani, Faisal Hadi Mohd Amizam and Meor Muhammad Zaman Meor Ahmad - Mohd Ghani, Mohd Sayuti; Mohd Amizam, Faisal Hadi; Meor Ahmad, Meor Muhammad Zaman (2011)
A study on chemical composition of three species of wood (Acacia, Sentang and Kelempayan) was conducted. All three species of wood were ground in a ball mill and screened to pass through a 60 µm mesh. The major chemical composition of fibers was determined according to TAPPI standard. Chemical composition studies showed that Sentang contained the highest percentage of moisture content (14.99%), cold water solubility (19.92%), hot water solubility (17.01%), lignin (26.39%) and 1% NaOH solubility (23.36%). It also showed that extractive content was highest in Acacia (82.14%). Kelempayan exhibited the highest percentage of ash content (0.60%).